Removal of Neutral Red from Aqueous solutions usingSr2CaBO5.5 (B= Nb+5& Ta+5) - A. Awin Labib.; A. El-Rais Mahmoud.; M. Abo Salem Tasniem.; K. Almhidwi Salwa.; Alnaas Maryam.M.; Hadoud Ramadan.A.; F. Alzarzah Salah. (Journal of New Developments in Chemistry, 2022)
Two samples of the defectdouble perovskites with general formula Sr2CaNbO5.5 and Sr2CaTaO5.5 were synthesized and their cap abilities in the removal of neutral red dye investigated. Both samples have faced cubic perovskite-type structure in space group Fm3m. The replacement of Nb5+ by Ta5+ has influenced both crystal size and density of the two oxides but showed no impact on the removal capacities. The crystallite size of Sr2CaNbO5.5 and Sr2CaTaO5.5 was determined to be 93.56 and 43.69 nm respectively. The maximum removal capacities of Neutral red are found to be 190.5 mg/g using both the two oxides. This result is consistent with the cell volumes which displayed similar values. The removal of Neutral Red has a negative relationship with temperature but steadily increases as pH increased.
Keywords: Removal